2000
DOI: 10.1046/j.1365-2672.2000.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a commercial starter culture addition on the ripening of an artisanal goat's cheese (Cameros cheese)

Abstract: D P. TO R RE . 2000. The evolution of physicochemical parameters, and the most important microbial groups, were determined for the following three batches of 'Cameros' goat's milk cheese during ripening: Batch R elaborated with raw milk, Batch RS elaborated with raw milk and with the addition of a starter culture, and Batch PS elaborated with pasteurized milk and with the addition of the same culture. No differences in total solids (TS) or in the content of NaCl, fat and total nitrogen (expressed as percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
(51 reference statements)
6
25
2
Order By: Relevance
“…Low levels of enterococci were isolated during the initial ripening period but not thereafter. The presence of this bacterial group in cheese seems to vary depending upon the type of cheese, and this presence has been associated with the use of raw milk (11,33,38) and also the season when the cheese is made. As far as non-LAB populations are concerned, no Enterobacteriaceae were detected and 10 4 CFU/g of staphylococci were found in the final product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low levels of enterococci were isolated during the initial ripening period but not thereafter. The presence of this bacterial group in cheese seems to vary depending upon the type of cheese, and this presence has been associated with the use of raw milk (11,33,38) and also the season when the cheese is made. As far as non-LAB populations are concerned, no Enterobacteriaceae were detected and 10 4 CFU/g of staphylococci were found in the final product.…”
Section: Discussionmentioning
confidence: 99%
“…Although these organisms are usually present at low levels in curd (10 2 to 10 3 CFU/g), their concentrations increase during ripening to 10 7 to 10 8 CFU/g (15,21). NSLAB have been reported to be responsible for many of the flavor qualities of cheese, and their use as adjuncts to starter cultures might either improve taste or introduce off-flavors, depending upon the strains used (4,38,43).…”
mentioning
confidence: 99%
“…Olarte et al [82] observed differences in S. aureus growth in dependence on the addition of starter culture. In cheese without added starter culture, S. aureus exceeded concentrations higher than 5 log counts in 5 days.…”
Section: Effect Of Ph Value and Lab Presence On S Aureus Growth In Milkmentioning
confidence: 99%
“…Zeytineli cheese produced with natural rennet had a higher lactic acid bacteria population than did Germiyan cheese that was produced with commercial rennet (data not shown). Olarte et al (2000) reported the relation of lactic acid bacteria and initial lactic acid formation. Hatzikamari et al (1999) also observed higher initial levels of lactic acid bacteria in low-pH cheeses.…”
Section: Changes During Production and Ripeningmentioning
confidence: 99%